Minimally Invasive Ascending Aortic Replacement with Concomitant Aortic Valve Replacement, A Case Report - Gupta, Saikat Das; Haider, Ali; Chanda, Prasanta K; Adhikary, Dipal K (University Heart Journal, 2024)
Aortic valve stenosis or aortic stenosis is a type of heart valve disease (valvular heart disease). The valve between the lower left heart chamber and the body’s main artery (aorta) is narrowed and doesn’t open fully. This reduces or blocks blood flow from the heart to the aorta and to the rest of the body. Here we will discuss the care of a young male who presented with exertional dyspnea with palpitation and after detailed examination and investigation he was diagnosed as a care of severe aortic stenosis with moderate aortic regurgitation with bicuspid aortic valve and ascending aortic dilatation. University Heart Journal 2023; 19(2): 71-73